2013
DOI: 10.7547/1030165
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Footwear and Walking Distance on Gait Stability in Diabetic Patients with Peripheral Neuropathy

Abstract: This study suggests that gait alteration in patients with DPN is most pronounced while walking barefoot over longer distances and that footwear may improve gait steadiness in patients with DPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 46 publications
3
42
0
1
Order By: Relevance
“…Previous studies have demonstrated that peripheral neuropathy and fear of falling are linked to changes in gait performance, 4,26,3134 and the present findings are in good agreement with these. Patients with DPN, for example, are known to adopt a conservative walking strategy, with a longer double-support phase and generally slower stride velocities compared with patients without DPN.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have demonstrated that peripheral neuropathy and fear of falling are linked to changes in gait performance, 4,26,3134 and the present findings are in good agreement with these. Patients with DPN, for example, are known to adopt a conservative walking strategy, with a longer double-support phase and generally slower stride velocities compared with patients without DPN.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, these findings suggest that there is an apparent mismatch between perceived risk of falling and actual risk of falling in older adults with diabetes mellitus. This is important because gait performance declines with DPN 26,27 and places individuals with DPN at greater risk for fall events. 2830 However, our work suggests, worsening gait performance is not always accompanied by a greater fear of falling.…”
Section: Discussionmentioning
confidence: 99%
“…With a custom-made foot plate, gauntlet styling enabling plantar and dorsi flexion of the foot, the AFO might have improved proprioception (Hijmans et al, 2007) due to increased skin contact at the plantar aspect of the foot (Najafi et al, 2013b) as well as the shin area (Feuerbach et al, 1994) in contrast to the standard shoes.…”
Section: Discussionmentioning
confidence: 98%
“…One potential explanation could be the DFO's contoured arch could have contributed to improved gait parameters. 16 Our prior work demonstrated that custom foot orthoses reduced gait variability and medial and lateral COM displacement 16 that may be the result of improved proprioceptive feedback. 16,25 The custom foot orthoses tested in these studies used top covers that were glued to the underlying contoured shell and they did not allow freedom movement within top cover layers as the DFO in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…There was a 5-minute acclimatization period without weight-bearing, shoes, or socks prior to baseline thermal imaging and standardized walking stress test. 15 In random sequence, each insole condition was tested for gait during habitual speed, 16 balance in tandem stance with eyes open and closed, 17 and a thermal image was taken after 200 steps of walking stress. To explore whether reducing shear force may impact risk of falling, gait was also examined during dual task (walking while counting backward), which is a more sensitive paradigm than single task (walking alone) to evaluate risk of falling.…”
Section: Methodsmentioning
confidence: 99%